SARA MILLS’ CRITICAL DISCOURSE ANALYSIS ON ONLINE NEWS ARTICLES ABOUT VIOLENCE CASES AGAINST WOMEN - Aos Sogiri; Iceu Siti Nurhasanah (JLER (Journal of Language Education Research), 2022)
This study focused on discussing violence among women in online media news. Good media can convey balanced information. Some news related to violence against women can be represented in a different discourse. Currently, the exploitation of women is carried out through more intellectual and well-packaged ways, one of which is through discourses published in the mass media, especially online media. Women in the mass media are positioned to stand out visually but are very marginalized in meaning. Suppose things like this continue to be left unchecked. In that case, it will emphasize the existence of gender inequality between women and men which has implications for increased violence and gender oppression with women who are always the victims. The problem discussed in this study is critical discourse analysis using the Sara Mills model. Sara Mills' discussion of feminist discourse theory is the center of her study. In addition, it also discusses women's issues, such as how women are represented in texts, pictures, photos, and in the news. This research examines how the text becomes biased in presenting women and how the marginalization of women is formed in weakening the position of women.